Versatile direct-writing of dopants in a solid state host through recoil implantation - Johannes E. Fröch (Nature Portfolio, 2020)
Direct writing of active defects is a much sought-after step towards scalable quantum technologies. Here, the authors show a flexible approach by transferring momentum from an ion beam to thin films pre-deposited onto diamond surfaces (using films of Si, Ge, Sn or Pb) or fiber cores (using Eu).